Proinflammatory and Cytotoxic Effects of Hexadecylphosphocholine (Miltefosine) against Drug-Resistant Strains of Trypanosoma cruzi - Saraiva, Victor B. (American Society for Microbiology, 2002)
The increased resistance of the protozoan parasite Trypanosoma cruzi to nitro derivatives is one of the major problems for the successful treatment of Chagas' disease. In the present study, we have tested the effects of 1-O-hexadecylphosphocholine (miltefosine) against strains of T. cruzi that are partially resistant (strain Y) and highly resistant (strain Colombiana) to the drugs in clinical use. As expected, epimastigotes of strain Colombiana showed higher levels of resistance to benznidazole than those of strain Y. However, the level of resistance to miltefosine was the same for both strains. This alkylphospholipid was also extremely toxic against intracellular amastigotes of both strains. This ether-lipid analogue induced in a dose-dependent manner the production of tumor necrosis factor alpha and nitric oxide (NO) radicals by infected and noninfected macrophages, suggesting that miltefosine may activate macrophages in vitro. Nevertheless, the cytotoxic effect of miltefosine against intracellular amastigotes was independent of the amount of NO produced by the infected macrophages since the same dose-response curves for miltefosine were observed when the NO production was blocked by the NO synthase inhibitor N(G)-monomethyl-l-arginine monoacetate. Preliminary in vivo studies with BALB/c mice infected with strain Y indicated that oral miltefosine promoted survival and reduced the parasitemia to levels comparable to those observed when benznidazole was used. Four months after treatment, no parasites were detected in the blood or spleen tissue sections maintained in culture. Together, these results support the hypothesis that miltefosine may be used for the treatment of Chagas' disease, including cases caused by resistant strains of T. cruzi.